PENGARUH LEADER MEMBER EXCHANGE(LMX) DAN PERSON-ORGANIZATION FIT(PO-FIT) TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOUR(OCB) DENGAN KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA SEBAGAI VARIABEL - Jati Prabawa, Aditya; Abdul Rozak, Hasan (Proceeding SENDI_U, 2016)
This study aims to determine the effect of Leader Member Exchange and Person Organization Fit to rganization Citizenship Behavior with Organizational Commitment and Job Satisfaction as anintervening variable. Research was conducted on the staff of the BKD Central Java province with a number of respondents as many as 139 people. The research instrument used in the form ofquestionnaires were tested for validity and reliability, and to explain the influence of independent variables on the dependent variable using a multiple linear regression equation, whereas hypothesistesting using Simultaneous significance test,Individual arameter significance testand beta coefficient. The results showed that (1) Leader Member Exchange positive and significant impact onthe Commitment Organizational (2) Person Organization Fit influential positive and significant impact on the Commitment Organizational (3) Leader Member Exchange positive and significant impact on job satisfaction (4) Person Organization Fit positive and significant impact on job satisfaction (5) Leader Member Exchange positive and significant impact on the Organization Citizenship Behavior (6) Person Organization Fit not significant to the Organization Citizenship Behavior (7) Commitment Organizational not significant to the Organization Citizenship Behavior (8) Job Satisfaction positive and significant impact on the Organization Citizenship Behavior.Keywords : Leader Member Exchange (LMX), Person-Organization Fit (P-O Fit), Organization Citizenship Behavior (OCB), Organizational Commitment, Job Satisfaction